The modern quantum computing tools invstigation - Bozhko, I.; Chetverykov, G. G.; Karataiev, O. (ХНУРЕ, 2020)
The modern quantum computing tools invstigation The current paper covers the investigation of the current state of the existing tools for quantum programming including QCL (Quantum Computation Language), quantum pseudocode, Q# programming language and Quipper. Since quantum computing is one of the main research areas today, the respective tools are being created quite often. They are aimed on simplifying the development of quantum programs, on the one hand, and provide some platform for testing and running them, on the other hand. So, the authors investigated the currently available tools and provided the results in the article.
Keywords: quantum computing; quantum computer; quantum computing tools; microsoft quantum development kit